Invisibilité ou inaudibilité ? Ce que l’analyse de l’inaudibilité sociale fait au concept d’invisibilité - Élise Huchet (Terrains/Théories)
While the notion of social invisibility has been the focus of significant and relatively numerous works in the field of philosophy and the social sciences, the concept of social inaudibility, although very similar, has not received similar attention. Starting from this observation, the article aims to question the relationship between the two concepts and the corresponding phenomena, and defends the need for their articulation, against a purely analogical approach. The article then focuses on Axel Honneth’s thinking, highlighting the centrality of the question of social inaudibility in his work. Ultimately, the aim is to understand how the analysis of inaudibility can shed light on the phenomenon of social invisibility.